Fluid Overload and Self-Efficacy in Hemodialysis: Implications for Patient Care - Wilandika, Angga; Sanusi, Santy; Rahmawati, Rika (Journal of Public Health Sciences, 2025)
This study aimed to investigate the relationship between self-efficacy and fluid overload in patients undergoing hemodialysis. The study included 96 adult patients receiving regular hemodialysis at a private hospital in Bandung, Indonesia. Self-efficacy in fluid restriction was assessed using a validated 20-item questionnaire based on Bandura’s model. Overhydration was measured using the Interdialytic Weight Gain (IDWG) index. Descriptive and inferential analyses were performed, including Kendall’s Tau-b correlation test. The study revealed that 60.4% of participants had low self-efficacy, while 66.7% were classified as overhydrated. A statistically significant inverse relationship was found between self-efficacy and fluid overload (p = 0.002), suggesting that patients with lower self-efficacy were more likely to experience overhydration. Self-efficacy plays a critical role in fluid management among patients receiving hemodialysis. Strengthening self-efficacy through nurse-led behavioral interventions, standardized patient education, and digital health monitoring may enhance fluid adherence.